2016
DOI: 10.4252/wjsc.v8.i4.158
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal-associated invariant T cells from induced pluripotent stem cells: A novel approach for modeling human diseases

Abstract: Mice have frequently been used to model human diseases involving immune dysregulation such as autoimmune and inflammatory diseases. These models help elucidate the mechanisms underlying the disease and in the development of novel therapies. However, if mice are deficient in certain cells and/or effectors associated with human diseases, how can their functions be investigated in this species? Mucosal-associated invariant T (MAIT) cells, a novel innate-like T cell family member, are a good example. MAIT cells ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 106 publications
(163 reference statements)
1
7
0
Order By: Relevance
“…We initially compared the circulating levels of Mucosal-associated invariant T (MAIT) cells in BAV versus TAV cases with and without TAA. MAIT cells represent a novel innate-like T cell subsets consisting of 1%–10% of T cells in the peripheral blood [ 18 20 ]. They mediate a pivotal role in immune-dysregulated diseases and other pathologies, like infections, inflammatory diseases, and others [ 18 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We initially compared the circulating levels of Mucosal-associated invariant T (MAIT) cells in BAV versus TAV cases with and without TAA. MAIT cells represent a novel innate-like T cell subsets consisting of 1%–10% of T cells in the peripheral blood [ 18 20 ]. They mediate a pivotal role in immune-dysregulated diseases and other pathologies, like infections, inflammatory diseases, and others [ 18 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…MAIT cells represent a novel innate-like T cell subsets consisting of 1%–10% of T cells in the peripheral blood [ 18 20 ]. They mediate a pivotal role in immune-dysregulated diseases and other pathologies, like infections, inflammatory diseases, and others [ 18 20 ]. We observed that the mean blood levels of MAIT cells, expressed in absolute numbers, were significantly different between the BAV and the TAV groups, with and without TAA (see Figure 1(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…The state of immunoparesis characteristic of patients with ALD, especially patients with SAH, may be intensified by the combination of quantitative MAIT cell depletion and functional defects associated with the residual MAIT cell population. Ex vivo functionally reprogrammed MAIT cells, 14 51 MAIT cells derived from induced pluripotent stem cells (iPSC-derived MAIT cells) 60 and strategies aimed at restoring the gut barrier may represent novel attractive immunotherapeutic avenues for cirrhosis and alcoholic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs have the promise of achieving the MAIT cell response appropriate for the individual disease as an agonist or antagonist of MAIT cell activity. Other therapeutic possibilities are ex vivo re-programming of MAIT cell function with select cytokines[ 82 , 107 ], vaccination with IL-23 in combination with 5-OP-RU[ 217 ], and re-programming and re-differentiating MAIT cells using induced pluripotent stem cells derived from MAIT cells[ 223 ]. Glucocorticoids reduce MAIT cell frequency in certain immune-mediated diseases[ 15 , 177 , 185 ], and they also may have a role in modulating MAIT cell activity.…”
Section: Incorporating Mait Cells Into the Pathogenesis Of Chronic Liver Diseasementioning
confidence: 99%